Perbandingan Mutu Tempe Dari Kacang Kedelai Dengan Kacang Tanah - Ahsanunnisa, Riska (ALKIMIA, 2018)
Tempe is traditional Indonesian food that has been known for a long time. Research on the quality of tempe with variations of peanut and soybean aims to see the variation of tempe making using peanut and soybean. Quality testing in this study through organoleptic test and chemical analysis such as water content, and ash content. The result of organoleptic test on flavour showed that panelist preferential T2 much higher than T1. The average water content respectively were 59,11% for soybean and 55,17% for peanut. Meanwhile the average ash content the highest were soybean 0,67% and for the peanut were 0,59%.